Reports in Transition — The Case of Business Data Visualization in Ideal Keittiöt Oy - Salminen, Kari (My University, 2020)
The aim of this thesis was to develop three new relevant Qlik Sense reports for Ideal Keittiöt Oy, which is a Finnish company selling kitchen and sanitary fixtures. Ideal Keittiöt Oy had been using a custom-built enterprise resource planning system named Tarla with a customized Pentaho Reporting embedded in it since 2011. In 2017, a switch to Jeeves ERP and Qlik Sense was initiated out of business needs. The end-users of the new reports were to be the management staff and a few select employees. The Jeeves ERP’s database was also to be partly documented for reporting purposes. The use statistics of Pentaho Reporting’s reports were analyzed and the end-users were interviewed about their reporting needs. In March 2018, based on this information two new reports were selected to be implemented. One new Qlik Sense report was implemented: an ABC analysis of sales deliveries using Tarla’s data, because data from Jeeves ERP was not yet available. Research on visual perception was used in the new report for the effective visualization of data. In 2019, Jeeves ERP was deployed in Ideal Keittiöt Oy. In November 2019, an internal guide for using Jeeves ERP’s database in reporting was written for Ideal Keittiöt Oy as a master’s project, which partially satisfied this thesis’s aim related to documentation. Three new reports had originally been aimed for, two had been selected to be implemented and one had been finally implemented. This new report looked quite good and was moderately easy to use, but was not useful anymore in 2020 because it did not use Jeeves ERP’s data.

Tämän tutkielman tavoitteena oli kehittää kolme uutta merkityksellistä Qlik Sense -raporttia Ideal Keittiöt Oy:lle, joka on suomalainen keittiö- ja saniteettikalusteita myyvä yritys. Ideal Keittiöt Oy oli käyttänyt Tarla-nimistä erikoisvalmisteista toiminnanohjausjärjestelmää siihen sulautetun räätälöidyn Pentaho Reportingin kanssa vuodesta 2011 alkaen. Vuonna 2017 käynnistettiin liiketoiminnallisten tarpeiden perusteella vaihto Jeeves ERPiin ja Qlik Senseen. Uusien raporttien loppukäyttäjien oli tarkoitus olla johtohenkilöstö ja harvat valitut työntekijät. Tässä työssä oli tarkoituksena myös osittain dokumentoida Jeeves ERPin tietokanta raportointitarpeita varten. Pentaho Reportingin raporttien käyttötilastoja analysoitiin ja loppukäyttäjiä haastateltiin heidän raportointitarpeisiinsa liittyen. Maaliskuussa 2018 näiden tietojen perusteella valittiin kaksi uutta raporttia toteutettaviksi. Yksi uusi Qlik Sense -raportti toteutettiin: myyntitoimitusten ABC-analyysi Tarlan dataa käyttäen, koska Jeeves ERPin dataa ei ollut vielä saatavilla. Näköaistitutkimusta käytettiin uudessa raportissa datan tehokkaaseen visualisointiin. Vuonna 2019 Jeeves ERP otettiin käyttöön Ideal Keittiöt Oy:ssa. Marraskuussa 2019 kirjoitettiin erikoistyö Ideal Keittiöt Oy:n sisäinen ohje Jeeves ERP -raportointiin, mikä osittain täytti tämän tutkielman tavoitteen dokumentointiin liittyen. Alunperin oli tavoiteltu kolmea uutta raporttia, kaksi oli valittu toteutettaviksi ja lopulta yksi oli toteutettu. Tämä uusi raportti näytti melko hyvältä, oli kohtuullisen helppo käyttää, mutta ei ollut enää hyödyllinen vuonna 2020, koska se ei käyttänyt Jeeves ERPin dataa.
Keywords: information visualization, data visualization, business intelligence, ERP, enterprise resource planning system, SME